Desain dan analisis chassis tipe tubular space frame - M. Wildanul Kahfi; Nely Ana Mufarida; Kosjoko Kosjoko (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2023)
Automotive is one of the mainstay products in the world today, especially in 4-wheeled vehicles and 2-wheeled vehicles. One of them is electric cars whose main driving force uses electric power. Some of the advantages possessed by electric vehicles with oil-fueled vehicles include free air police from exhaust fumes, no odor and a smoother motor sound. The development of electric cars in Indonesia, which is now growing rapidly, especially among university students, is being held with competitions to make electric cars that are worthy of being marketed. For that we need an energy-efficient car chassis design that is in accordance with the regulations of the Indonesian Electric Car Competition (KMLI). Research on the design chassis in previous studies has been done with different dimensions, materials, and types of chassis used. The purpose of this research is to design and analyze chassis type Tubular Space Frame using Solidworks 2019 Software in the hope of producing a chassis that is strong, lightweight and has flexibility properties while still paying attention to the Factor of Safety (FOS) when used. The chassis designed using Solidwork 2019 software has dimensions, including: Length = 1883.40 mm, Height = 1033.40 mm, Width = 721.34 mm. The results of the analysis and determination of the material between Aluminum 6061-T6 and Aluminum 6063-T6 used with a comparison of the values ​​of stress, displacement, and safety of factors that occur in the frame, it can be concluded that the chassis is a tubular type with the use of pipes 34.4 x 26.64 3.38 mm thick and 21.36 x 15.50 mm thick 2.77 mm is the most secure chassis and the weight is quite light.